1977
DOI: 10.1159/000240982
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Metabolism of <sup>14</sup>C-Palmitate by Fetal Rabbit Tissues

Abstract: The uptake and esterification of 14C-palmitate into lipid classes in placenta, fetal brown adipose tissue (BAT) and liver of rabbits were investigated in vitro. Fetal BAT showed a high rate of fatty acid uptake, 8.5 μmol·h––1 tissue·h––1. From 5 min onwards, the majority of incorporated label was in the triglyceride fraction. The placenta and fetal liver also incorporated 1-[14C]-palmitate into both FFA and esterified lipid fractions, although at much lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…No anabolism has been observed in pregnant rabbits (Lebas, 1975 (Elphick et al, 1975 ;Elphick and Hull, 1977a,b ;Hudson and Hull, 1977 ;Stammers et al, 1983 Robinson and Williamson, 1980). The only data available have shown that blood ketone bodies remain very low throughout pregnancy in rabbits (Gilbert et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…No anabolism has been observed in pregnant rabbits (Lebas, 1975 (Elphick et al, 1975 ;Elphick and Hull, 1977a,b ;Hudson and Hull, 1977 ;Stammers et al, 1983 Robinson and Williamson, 1980). The only data available have shown that blood ketone bodies remain very low throughout pregnancy in rabbits (Gilbert et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper (Hudson and Hull, 1977), it was found that the uptake of label per unit weight of fetal BAT in vitro was much greater than that of fetal liver and that the rate of fatty acid uptake by fetal BAT in vitro could account for up to 70% of the fat deposited in the tissue during the last 4 days of gestation. The difference between the results obtained in vitro and those in vivo can be attributed to the route of the fetal circulation, which enters the liver directly from the umbilical vein before passing into the rest of the circulation.…”
Section: Discussionmentioning
confidence: 91%
“…Thin-layer chromatography (TLC) of plasma samples was performed as described by Elphick et al (1975) and TLC of tissue samples as described by Hudson and Hull (1977). Recovery of radioactivity from TLC plates was: placenta 84 ± 2%, liver 96 ± 1% and BAT 94 ± 2% (mean ± SEM; n = 24).…”
Section: Methodsmentioning
confidence: 99%
“…Fetal adipose tissue may have the capacity to regulate its own composi tion, as in the adult (20). If the pattern laid down reflects the composition of a fatty acid pool that exchanges with adipose tissue triglyc eride fatty acids and plasma FFA (12), then the possibility of a fatty acid accumulating in fetal adipose tissue to an extent greater than its relative abundance in fetal plasma FFA might be less likely.…”
Section: Discussionmentioning
confidence: 99%